PENERAPAN SISTEM MANAJEMEN OPERASIONAL DI PT. SUPER MANDIRI PRATAMA KOTA BATAM - Angela; Fendy Cuandra; Jesslin Clorina; Angelina; Supriyadi Arifin (Lembaga Riset dan Inovasi Kreyat Center, 2023)
PT. Super Mandiri Pratama is a manufacturing company founded on December 25, 2000, engaged in glass renovation, construction and production. During 22 years of existence, PT. Super Mandiri Pratama has successfully competed in a competitive industry and has built and maintained a good reputation. The research method used is descriptive qualitative research, the data sources used are primary that was obtained from observation and interview and secondary data obtained from various sources of library materials which contained various matters relating to operational management. The purpose of this research is to analyze the implementation of operational management at PT. Super Mandiri Pratama. Results showed that the company implemented human resource management, project management, and supply chain management in a proper and structured manner. However, the company does not set a location strategy, so the authors suggest companies to implement location strategy in order to minimize transportation costs and achieve work effectiveness.